Role of epigenetic m6A RNA methylation in vascular development: mettl3 regulates vascular development through PHLPP2/mTOR‐AKT signaling. Issue 5 (31st March 2021) - Parial, Ramendu; Li, Hui; Li, Jia; Archacki, Stephen; Yang, Zhongcheng; Wang, Isabel Z.; Chen, Qiuyun; Xu, Chengqi; Wang, Qing K.
Abstract: N 6 ‐methyladenosine (m6A) methylation is the most prevalent RNA modification, and it emerges as an important regulatory mechanism of gene expression involved in many cellular and biological processes. However, the role of m 6 A methylation in vascular development is not clear. The m 6 A RNA methylation is regulated by dynamic interplay among methyltransferases, binding proteins, and demethylases. Mettl3 is a member of the mettl3‐mettl14 methyltransferase complex, referred to as writers that catalyze m6A RNA methylation. Here, we used CRISPR‐Cas9 genome editing to develop two lines of knockout (KO) zebrafish for mettl3 . Heterozygous mettl3 +/− KO embryos show defective vascular development, which is directly visible in fli‐EGFP and flk‐EGFP zebrafish. Alkaline phosphatase staining and whole mount in situ hybridization with cdh5, and flk markers demonstrated defective development of intersegmental vessels (ISVs), subintestinal vessels (SIVs), interconnecting vessels (ICVs) and dorsal longitudinal anastomotic vessels (DLAV) in both heterozygous mettl3 +/− and homozygous mettl3 −/− KO zebrafish embryos. Similar phenotypes were observed in zebrafish embryos with morpholino knockdown (KD) of mettl3 ; however, the vascular defects were rescued fully by overexpression of constitutively active AKT1 . KD of METTL3 in human endothelial cells inhibited cell proliferation, migration, and capillary tube formation. Mechanistically, mettl3 KO and KD significantly reduced the levels of m 6 A RNA methylation, and AKT phosphorylation (S473) by an increase in the expression of phosphatase enzyme PHLPP2 and reduction in the phosphorylation of mTOR (S2481), a member of the phosphatidylinositol 3‐kinase‐related kinase family of protein kinases. These data suggest that m 6 A RNA methylation regulates vascular development via PHLPP2/mTOR‐AKT signaling.